Adaptive effects of parental and developmental environments on offspring survival, growth and phenotype. (10th November 2022) - Cortese, Daphne; Crespel, Amélie; Mills, Suzanne C.; Norin, Tommy; Killen, Shaun S.; Beldade, Ricardo
Abstract: Phenotypic adjustments to environmental variation are particularly relevant to cope with putative environmental mismatches often imposed by natal dispersal. We used an intergenerational cross‐transplant field‐based experiment to evaluate the morphological and physiological effects of parental and postsettlement water flow environments on the orange‐fin anemonefish Amphiprion chrysopterus through ontogeny (at pre‐ and postsettlement stages). Offspring born from parents under high water flow had an 18% higher caudal fin aspect ratio (a compound measure of shape) at the presettlement stage, 10% slower growth after settlement, and 55% lower survival after settlement compared to offspring from low water flow parents. At the presettlement stage, caudal fin length was determined by parental caudal fin length. At the postsettlement stage, fish survived equally well with similar phenotypes in both high and low developmental flow environments. However, results suggest potential developmental phenotypic plasticity in caudal fin length, which increases more under low water flow during development. After settlement, growth was the only morphological or physiological trait that was associated with parental water flow, which was lower from parents under high flow, as was survival. These results give important insights into the parental contribution, both genetic and nongenetic, in determining early offspring phenotype and subsequent growth and survival. Our results also suggest that offspring may possess flexibility to cope with a wide range of local environments including those different from their parents. Overall, the findings of this study show the fitness consequences of living in different environments and the likely trade‐offs between parental and offspring fitness in a wild population. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.